2015
DOI: 10.1021/acs.inorgchem.5b00446
|View full text |Cite
|
Sign up to set email alerts
|

A Relativistic Quantum-Chemical Analysis of the trans Influence on 1H NMR Hydride Shifts in Square-Planar Platinum(II) Complexes

Abstract: Empirical correlations between characteristic (1)H NMR shifts in Pt(II) hydrides with trans ligand influence series, Pt-H distances, and (195)Pt shifts are analyzed at various levels of including relativistic effects into density-functional calculations. A close examination of the trans ligand effects on hydride NMR shifts is shown to be dominated by spin-orbit shielding σ(SO). A rather complete understanding of the trends has been obtained by detailed molecular orbital (MO)-by-MO and localized MO analyses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
116
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 62 publications
(128 citation statements)
references
References 58 publications
9
116
1
2
Order By: Relevance
“…As for the more restricted ligand set discussed above, we see that the overall trend is dominated by σ SO , but even σ p changes sign as a function of the ligand (Figure ). The latter point contrasts with our earlier observations for Pt II hydride complexes . We note in passing that the paramagnetic and SO shieldings are dominated by the shielding tensor components perpendicular to the H‐Au‐L bonding axes, whereas the parallel component does not change as much for the different ligands (cf.…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…As for the more restricted ligand set discussed above, we see that the overall trend is dominated by σ SO , but even σ p changes sign as a function of the ligand (Figure ). The latter point contrasts with our earlier observations for Pt II hydride complexes . We note in passing that the paramagnetic and SO shieldings are dominated by the shielding tensor components perpendicular to the H‐Au‐L bonding axes, whereas the parallel component does not change as much for the different ligands (cf.…”
Section: Resultscontrasting
confidence: 99%
“…Figure for neutral ligands; different correlation lines are obtained for neutral and anionic complexes; Figure S2 in the Supporting Information). However, similarly as found in our previous study of Pt II hydride complexes, the observed correlations between hydride shifts and Au‐H distances arise indirectly from the effect of the trans ligand on the polarization of the metal d (and p) orbitals, which in turn affects both the structures and the hydride shifts (see below).…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations